Opportunities and challenges of business 5.0 in emerging markets - Dadwal, Sumesh 1973-; Kumar, Pawan; Verma, Rajesh; gh, Gursimranjit (IGI Global, 2023)
This book provides insights on the impact of industrial revolution 5.0 offering various research perspectives on the implication of transformation of revolution from 1.0 to 5.0 for readers in both industry and academia to assist them in teaching and training the next generation leaders through universities and corporate training
Keywords: Industries -- Developing countries; Economic development -- Developing countries